Harnessing the Power of Alchemilla: A Natural Solution for Skin Health and Dermatological Disorders - Sebastian Kanak; Barbara Krzemińska; Anna Berecka-Rycerz; Monika Kopeć; Katarzyna Dos Santos Szewczyk (Molecules)
Skin diseases are prevalent and encompass a wide range of disorders with varying clinical manifestations and diverse etiopathogenesis. The response to the necessity of multidirectional treatment is provided by species belonging to the genus Alchemilla, which is used in traditional medicine as well as in cosmetic formulations. Responsible for the healing properties of these plants for skin diseases are mainly compounds such as tannins, phenolic acids, flavonoids, and anthocyanins. The aim of the study was to analyze and synthesize the published literature on the Alchemilla species in skincare with a timeframe of December 2024. The literature indicates that due to antioxidant, anti-inflammatory, astringent, antimicrobial, elastase activity and tyrosinase inhibitory properties of various Alchemilla species, extracts obtained from these plants can be successfully applied in skin rashes, acne, stretch marks, eczema, psoriasis, wrinkles and other dermatological issues. To the best of our knowledge, this is the first review of the cosmetic activities of Alchemilla species.